The Influence Of Consumer Behavior and Prices On Consumer Decisions to Buy Products At PT. Daikin Airconditioning Indonesia - Sri Rezeki; Muammar Rinaldi; Ihdina Gustina; Antonio Lodian (LPPM STIE EKA PRASETYA, 2022)
This study aims to determine the effect of consumer behavior on consumer decisions at PT. Daikin Airconditioning Indonesia, knowing the effect of price on consumer decisions at PT. Daikin Airconditioning Indonesia, knowing the influence of Consumer Behavior and Prices on Consumer Decisions at PT. Daikin Airconditioning Indonesia. The research methodology used is descriptive quantitative method. The type of data used in this study is quantitative data, namely data obtained in the form of numbers or numbers. Sources of data in the form of primary data and secondary data. Primary data obtained from the results of distributing questionnaires to respondents, secondary data obtained from data and literature relating to the problems discussed. The research population that will be used in the study are all consumers who make purchases at the company during the 2021 period as many as 15,336 consumers. By using the Slovin formula with an error rate of 10%, the number of samples obtained is 100 respondents. Data were analyzed using multiple linear regression analysis method. The results showed that consumer behavior and prices had a positive and significant effect on consumer decisions at PT. Daikin Airconditioning Indonesia